Application of digital particle image velocimetry to insect aerodynamics: measurement of the leading-edge vortex and near wake of a Hawkmoth - Bomphrey, Richard J.; Lawson, Nicholas J.; Taylor, Graham K.; Thomas, Adrian L. R. (Springer, 2007)
Some insects use leading-edge vortices to generate high lift forces, as has been inferred from qualitative smoke visualisations of the flow around their wings. Here we present the first Digital Particle Image Velocimetry (DPIV) data and quantitative analysis of an insect’s leading-edge vortex and near wake at two flight speeds. This allows us to describe objectively 2D slices through the flow field of a tethered Tobacco Hawkmoth (Manduca sexta). The near-field vortex wake appears to braodly resemble elliptical vortex loops. The presence of a leading-edge vortex towards the end of the downstroke is found to coincide with peak upward force production measured by a six-component force–moment balance. The topology of Manduca’s leading-edge vortex differs from that previously described because late in the downstroke, the structure extends continuously from wingtip across the thorax to the other wingtip.